Conscientiousness, self-efficacy, social support and health information-seeking behaviour of senior secondary school adolescents in Ibadan North Local Government Area of Oyo State (2018)
In recent tunes, it has been observed that poor knowledge on health state and status has led to high morbidity and mortality. There is prevalence in poor health-information knowledge, ignorance, increased STIS, HIV/AID, risky health behaviour, abortion and the like. The danger posed by poor health knowledge motivated an investigation of the health information-seeking behaviour of adolescents using conscientiousness, self-efficacy and social support as predictors. The study adopted a correlational study with a sample of 200 adolescents randomly sampled from Ibadan North local Government Area of Oyo State. Four reliable measuring instruments were used to collect data. Three research questions raised analysed were using Pearson product moment correlation and multiple regression analysis. The result showed that conscientiousness, self-efficacy and social support positively correlated with health information-seeking behaviour. The regression analysis showed that the three factors jointly accounted/or 42.2% of the total variance in adolescent information-seeking behaviour. Social support was found to be the strongest predictor followed by self-efficacy and conscientiousness. Among others recommendations, parents, teachers and significant individuals are enjoined to help students out with their demand to know much about their health status. School counsellors are admonished to help students to build their self-efficacy to help them to he bald enough to seek for health information. The government should also employ school counselors who will assist students to build their personality (conscientiousness) to enhance self-control on their health issues. This might go a long u-«v in reducing self-prescription and misuse of drug